ONTINUING PROFESSIONAL PHYSICAL EDUCATION IN THE INTERNAL AFFAIRS BODIES - H. Arov; D. Petrenko; K. Marinchenko; D. Gladkikh; A. Kudrya (Вестник Северо-Кавказского федерального университета, 2022)
The article is devoted to the study of the problems of continuous professional physical education in the internal affairs bodies and is dictated by the importance ofphysical readiness, which at first glance does not cause visible doubts, as an important component of the overall combat readiness of employees. This fact fundamentally characterizes the role ofphysical training, which acts as one of the main subjects of service and combat training, as well as being an effective pedagogical tool and energy basis for training and education. The analysis of the obtained results allows us to define a single concept of the development of the system of continuous professional physical education in the internal affairs bodies, the essence of which is reduced to the need for the gradual formation of the foundations ofpedagogical skills in accordance with the multi-level structure of legal education.